Orientalisme dan Hadits : Kritik terhadap Sanad Menurut Pemikiran Joseph Schacht - Irzak Yuliardy Nugroho (Asy-Syari’ah : Jurnal Hukum Islam, 2020)
The Origins of Muhammadan Jurisprudence is the work of Joseph Schacht which is the foundation of Islamic scholarship in the West. This is the main book about the field of study which later was known as "orientalism of Islamic law". Not only was it phenomenal, this book was also controversial. Schacht's work received rave reviews from leading orientalis, H.A.R. Gibb, for example, considers that the book will be the foundation for all future studies of society and Islamic law, at least in the West. As the title suggests, the Origins did discuss the intricate issues surrounding the early history of the formation and origins of Islamic law, the day of its birth and its originality. Joseph Schacht argued that the emergence of classical fiqh schools, then the consequence of the emergence of hadith experts and according to him, hadith experts had falsified the hadith to defeat the rules made by fiqh expert groups, Theory of Projecting Back and Common Link, the theory of the results of Schacht as a theory of reconstruction of the occurrence of sanad hadith. To get a justification for Schacht's opinion on the backward projection of the Hadith and connect it with important figures from the previous period, then connected back to friends and finally to the prophet. So that it can be said that the Qur'an and Hadith do not contribute to the formation of Islamic law. Musthafa Azami broke the Scacht theory about projecting back with the explanation, that fiqh had developed since the time of the Prophet. Fiqh is ijtihady. Therefore, it is difficult to accept the opinion of Schacht that fiqh only developed during the appointment of Qadhi during the Umayyad Dynasty.Keywords: Orientalism, Sanad, Hadits